Intersectional theology : an introductory guide - Kim, Grace Ji-Sun, 1969-; Shaw, Susan M. (Susan Maxine), 1960- (Fortress Press, 2018)
Intersectional Theology: An Introductory Guide offers a new approach to theology that encourages centering of social differences and structures of power in the ways we think about God, the church, and other theological categories. Rooted in intersectionality, a tool of analysis developed primarily by black feminists, intersectional theology calls for examination of theological ideas from multifaceted and ever-changing perspectives that move us toward social justice.